Pengelolaan Dana Pinjaman Modal Dalam Rangka Pengembangan Usaha EkonomiI Kecil:Studi Deskriptif Pada Program Pinjaman Modal Usaha Dalam Proyek Pemberdayaan Anak, Keluarga dan Komunitas di RW 03 Kelurahan Kemiri Muka, Depok, Jawa Barat - Oktavia, Yesi (UI Scholars Hub, 2006)
Economic empowering is the most popular program that applied to alleviate the poverty. Giving a capital to develop a small enterprise is becoming one of the most important issues that is need more attention. This issue concerning how the receivers could manage a number of capitals, because small enterprise management correlates with the outcome of the program that is to develop an entrepreneurship. From this outcome will be get that the receivers who come from the poor community are improving their family income successfully.